Acute hunger modifies responses on the Three Factor Eating Questionnaire hunger and disinhibition, but not restraint, scales. (1st March 2017) - Yeomans, Martin R.; McCrickerd, Keri
Abstract: It is widely assumed that responses on the Three Factor Eating Questionnaire (TFEQ) represent long-term (trait) attitudes to eating behaviour. However, the questionnaire requires agreement with a number of food related statements, and it is possible that some are easier to agree with when assessed hungry than sated. To test this potential state-dependency, participants completed a 100 mm visual analogue scale rating of their current hunger at the time they completed the TFEQ. Data were collected from two cohorts: Cohort 1 (507 women and 119 men) completed both measures on paper, while the hunger rating was computerised in Cohort 2 (179 women). Regression analysis revealed significant effects of rated hunger on scores on the hunger (TFEQ-H) and disinhibition (TFEQ-D) but not restraint (TFEQ-R) subscales, with higher TFEQ-H and TFEQ-D scores when participants were more hungry. In addition, 61 women and two men from Cohort 1 completed the measures on two separate occasions. Here, scores on TFEQ-H were higher on days when these participants were hungrier, but no differences in TFEQ-D or TFEQ-R were found. Overall these data suggest TFEQ-H could be interpreted as an indirect measure of current hunger, that scores on TFEQ-D are partly moderated by hunger but TFEQ-R is a more trait-like measure of restraint.